Competitiveness of Indonesian Crude Coconut Oil Export in Destination Countries - Tri Fatma Mala Yulhar; Dwidjono Hadi Darwanto (Agro Ekonomi, 2019)
This study aims to examine the competitiveness of Indonesian CCO in destination countries and examine what factors influence the competitiveness of Indonesian CCO in destination countries. The analytical methods used in this research were RCA, EPD, and panel data regression analysis. The time period used in this research was 1996 to 2017. The results of the study concluded that Indonesian CCO had competitiveness in the United States, the Netherlands, Malaysia, China, and Singapore. RCA index in each destination country showed that Indonesian CCO had a very strong comparative advantage. The EPD analysis showed that Indonesian CCO was in a rising star position in the Netherlands, Malaysia, China, and Singapore, while in the United States market Indonesian CCO was in a falling star position. The export volume of Indonesian CCO had positive effect, while trade openness of importing countries and export value of Philippines CCO had negative effect on the competitiveness of Indonesian CCO. The government and CCO exporters need to lobby the destination countries to import CCO from Indonesia, and to convince the destination countries, the quality of the CCO needs to be improved, so that Indonesian CCO will become more competitive than others.